An uncertain inventory model for deteriorating products with imperfections, variable selling price, partial backlogging and selling price dependent time varying demand. (2nd August 2019) - Mukhopadhyay, Arindum
Imperfect items are unavoidable in inventory systems because of imperfect production, human-errors, damages, etc. In this competitive world, demand of a newly launched hi-tech products decreases over time because some better quality items are available in the market at the same or less price. This situation pushes the manufacturers to reduce selling price so that demand of that item may increase. Also many customers prefer to buy from other sellers when stock-out occurs. Keeping all these facts in mind, an inventory model is developed for imperfect items with decreasing selling price, waiting time dependent backlogging and selling price dependent time varying demand subject to constant deterioration rate adopting the techniques from uncertain programming, the above model is modified to an uncertain model with all the cost parameters as uncertain variables. Then the model is converted into equivalent expected value model and sensitivity of optimal policy is analysed.